1996
DOI: 10.1051/apido:19960302
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of two kinds of commercially available pollen on colony development and queen production in the bumble bee Bombus terrestris L (Hymenoptera, Apidae)

Abstract: Summary — The effects of two kinds of stored pollen (fresh and dried, kept in the freezer) on individuals and colonies of Bombus terrestris were investigated. The pattern of colony development, and the number and biomass of workers and males were similar for colonies fed on fresh-frozen pollen (FFP) and dried-frozen pollen (DFP). However, queens reared on DFP were smaller, had lower biomass, higher mortality and produced smaller colonies than queens reared on FFP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…Maurizio (1958) already discussed the degrading effects of several methods for conserving pollen. Ribeiro et al (1996) and Ptacek (2001) confirmed this in their studies comparing fresh and dried pollen. Not only the physical, but also the chemical properties play a role.…”
Section: Pollensupporting
confidence: 61%
“…Maurizio (1958) already discussed the degrading effects of several methods for conserving pollen. Ribeiro et al (1996) and Ptacek (2001) confirmed this in their studies comparing fresh and dried pollen. Not only the physical, but also the chemical properties play a role.…”
Section: Pollensupporting
confidence: 61%
“…Nectar and pollen are essential food sources for bees. In extensive commercial rearing, bumblebee colonies are normally fed with sugar syrup and fresh or fresh frozen pollen collected from pollen traps at honey bee hives (Ribeiro et al, 1996;Velthuis and van Doorn, 2006). Pollen is the sole source of protein in the diet and also provides all of the nutritional requirements for growth and development of the larvae, young adults, and colony (Heinrich, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical composition and nutritional value of pollen vary greatly depending on the botanical origin. Pollen may also be affected by Effects of pollen protein content on Effects of pollen protein content on B. terrestris B. terrestris factors such as drying, ageing, or storage conditions (Ribeiro et al, 1996). The protein content of pollen can also vary widely, ranging from 2.5 to 61% and is generally accepted as a reliable measure of its nutritional value (Roulston et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Some scientists investigated the role of pollens in the development of bumblebee colonies (Plowright and Pendrel, 1977;Sutcliffe and Plowright, 1988;Duchateau and Velthuis 1989;Ribeiro et al, 1993;Regali and Rasmont, 1995;Ribeiro et al, 1996;Genissel et al, 2002). These authors tested pollens based mainly on the following criteria: egg production, body size of adults, larva weight, adult mortality and longevity, brood rearing capacity and sperm production of males.…”
Section: Introductionmentioning
confidence: 99%